Chasing a dream against all odds - Eva Vivian; Betty Chewning; Constance Flanagan (BMC, 2022)
Abstract Background Youth of color growing up in poverty face many challenges that children from more affluent families never experience. These children often reside in disadvantaged neighborhoods with substandard housing, inadequate medical care, and under resourced schools. This places these children at risk for poor academic achievement, school dropout, abuse and neglect, behavioral and socioemotional problems, and physical health problems. In spite of these risks, some children "beat the odds" and overcome the challenges and adversities in their external contexts. The paper reports the findings of a draw-and-write activity designed to learn the processes whereby protective factors promote resilience from a child's point of view. Methods In this qualitative study, a draw-and-write activity was conducted with a convenience sample of 33 children, (23 females and 10 males of which 10 were Hmong, 11 were Middle Eastern, and 12 were African Americans) .The children were asked to make visual representations of resources (persons or things that, in their view, contribute to their wellbeing.) In depth interviews with a subset of 15 of the children was conducted to discuss the meaning of the images in their drawings. A summative content analysis of the visual and narrative data was performed using a resilience framework. Results Regardless of racial/ethnic background, parents, and especially mothers, were the main "person or thing" identified by these children living in poverty as helping them "make it thus far in life." Ninety seven percent of the participants in this study described their parent(s) as nurturing and supportive, enabling them to overcome obstacles and adversities within their environment. Forty five percent of participants identified their mother as a key anchor in their life Fifty eight percent of the African American children indicated that their parent(s) encouraged education to escape poverty. Conclusion The findings support that families, particularly parents have the strongest influence on supporting the resilience process in a child. These findings were consistent across ethnicity and gender. Families, particularly parents, should be the target of future interventions designed to produce resilient behaviors in youth of color living in poverty.